2013
DOI: 10.1111/bph.12018
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of tobramycin and a copper–tobramycin complex with superoxide dismutase‐like activity

Abstract: BACKGROUND AND PURPOSEAirway inflammation in cystic fibrosis (CF) patients is characterized by accumulations of neutrophils in the airway and T cells in bronchial tissue, with activation of platelets in the circulation. CF patients are routinely treated with systemic or inhaled tobramycin for airway infection with Pseudomonas aeruginosa. Clinical trials have indicated an anti-inflammatory effect of tobramycin beyond its bactericidal activity. Here, we investigate the anti-inflammatory properties of tobramycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
0
13
0
2
Order By: Relevance
“…There is little data on the immunomodulatory effects of tobramycin, although it has been suggested that at obramycin-copper complex may display anti-inflammatory properties. [25] We monitored the cytotoxic effects of amphiphilic tobramycin analogues in human monocytic THP-1 cells (ATCC TIB-202). Therelease of lactate dehydrogenase was monitored in the tissue culture (TC) supernatants after 24 hstimulation to assess cytotoxicity.…”
mentioning
confidence: 99%
“…There is little data on the immunomodulatory effects of tobramycin, although it has been suggested that at obramycin-copper complex may display anti-inflammatory properties. [25] We monitored the cytotoxic effects of amphiphilic tobramycin analogues in human monocytic THP-1 cells (ATCC TIB-202). Therelease of lactate dehydrogenase was monitored in the tissue culture (TC) supernatants after 24 hstimulation to assess cytotoxicity.…”
mentioning
confidence: 99%
“…[25] We monitored the cytotoxic effects of amphiphilic tobramycin analogues in human monocytic THP-1 cells (ATCC TIB-202). There is little data on the immunomodulatory effects of tobramycin, although it has been suggested that at obramycin-copper complex may display anti-inflammatory properties.…”
mentioning
confidence: 99%
“…Tobramycin [26,27] (Table 1) is widely used as an intravenous and inhaled therapy to treat P. aeruginosa lung infections. The improvement in lung function in treated CF patients suggests that inhaled tobramycin may have anti-inflammatory effects in addition to its bactericidal activity [26].…”
Section: Tobramycinmentioning
confidence: 99%
“…The improvement in lung function in treated CF patients suggests that inhaled tobramycin may have anti-inflammatory effects in addition to its bactericidal activity [26]. Gziut et al [26] reported tobramycin antiinflammatory properties in vitro related to its ability to bind copper, elevated in blood and sputum in CF: in fact, copper-tobramycin has intra and extracellular superoxide dismutase-like activity, with the potential to limit the expression of a wide range of adhesion molecules, inflammatory cytokines [28,29] and T-cell migration [28,30].…”
Section: Tobramycinmentioning
confidence: 99%